Peak flow as a predictor of cause-specific mortality in China: results from a 15-year prospective study of ~170,000 men. - Smith, M; Zhou, M; Wang, L; Peto, R; Yang, G; Chen, Z (2013)
BACKGROUND: Forced expiratory volume in one second (FEV1) is inversely associated with mortality in Western populations, but few studies have assessed the associations of peak expiratory flow (PEF) with subsequent cause-specific mortality, or have used populations in developing countries, including China, for such assessments. METHODS: A prospective cohort study followed ~ 170,000 Chinese men ranging in age from 40-69 years at baseline (1990-1991) for 15 years. In the study, height-adjusted PEF (h-PEF), which was uncorrelated with height, was calculated by dividing PEF by height. Hazard ratios (HR) for cause-specific mortality and h-PEF, adjusted for age, area of residence, smoking, and education, were calculated through Cox regression analyses. RESULTS: Of the original study population, 7068 men died from respiratory causes (non-neoplastic) and 22 490 died from other causes (including 1591 from lung cancer, 5469 from other cancers, and 10 460 from cardiovascular disease) before reaching the age of 85 years. Respiratory mortality was strongly and inversely associated with h-PEF. For h-PEF ≥ 250 L/min, the association was log-linear, with a hazard ratio (HR) of 1.29 (95% CI: 1.25-1.34) per 100 L/min reduction in h-PEF. The association was stronger but not log-linear for lower values of h-PEF. Mortality from combined other causes was also inversely associated with h-PEF, and the association was log-linear for all values of h-PEF, declining with follow-up, with HRs per 100 L/min reduction in h-PEF of 1.13 (1.10-1.15), 1.08 (1.06-1.11), and 1.06 (1.03-1.08) in three consecutive 5-year follow-up periods. Specifically, lower values of h-PEF were associated with higher mortality from cardiovascular disease and lung cancer, but not from other cancers. CONCLUSIONS: A lower value of h-PEF was associated with increased mortality from respiratory and other causes, including lung cancer and cardiovascular disease, but its associations with the other causes of death declined across the follow-up period.